Representation of Gender Roles in the Household in the Film Sore Istri dari Masa depan (Semiotic Analysis of John Fiske) - Rinalda Tatiyana Tjahyadi; Yumelda Sari (Journal of Creative Power and Ambition (JCPA), 2026)
This study aims to analyze the representation of gender roles in the household in the film Sore: Istri dari Masa Depan using John Fiske's semiotic analysis. Although the film presents a seemingly progressive futuristic narrative, the main issue addressed is whether it genuinely challenges domestic stereotypes or instead perpetuates patriarchal culture. Utilizing a qualitative descriptive-interpretive method, data was collected through scene observation and documentation, then analyzed across three semiotic levels: reality, representation, and ideology. The results indicate that the film does not represent an equal division of roles but rather operates as pseudo-feminism. At the reality level, the female character is burdened with emotional labor as the husband's caregiver and savior. At the representation level, cinematic techniques manipulatively romanticize the wife's suffering and sacrifices. At the ideology level, the film perpetuates patriarchal hegemony by reinforcing the myth of women as natural caregivers. In conclusion, the film uses the illusion of female independence as an aesthetic veil to maintain traditional patriarchal power structures in the domestic sphere.